Motorized botulinum toxin injection device: a pilot study on attitudes toward technology-assisted injection in novice and experienced cosmetic practitioners. (3rd July 2020) - Chalhoub, Xavier; Marchner-Palmer, Sara; Ghanem, Ali
ABSTRACT: This study was performed to investigate the user perception of a cordless, motorized electronically controlled delivery system for botulinum toxin type A. Forty-six post-graduate students of varying experience levels of botulinum toxin injections and four members of the faculty from the MSc programme in Esthetic Medicine at Queen Mary University London participated in a demonstration of a motorized injection device. Thereafter, they performed a number of injections on a high fidelity silicone simulation model before completing a nine-item questionnaire. The more experienced injectors tended to appreciate the accuracy of the device more than the less experienced participants. Seventy-eight percent of participants said the device improved accuracy, particularly when administering small doses. Eighty-four percent leaned toward a favorable general view of the device. Forty-seven percent would possibly consider purchasing the device. Sixty-one percent would consider recommending the device to a colleague. The main advantage of the motorized injection device was the improved accuracy enabling delivery of small and precise doses. This may open up the possibility of new approaches to botulinum toxin treatments.